Cryopreservation of cherry rootstock Gisela 5 (Prunus cerasus × Prunus canescens) shoot tips by droplet-vitrification technique - Ružić Djurdjina; Vujović Tatjana; Cerović Radosav (Journal of Horticultural Research, 2013)
The droplet-vitrification technique was applied to in vitro shoot tips of cherry rootstock Gisela 5 (Prunus cerasus × Prunus canescens). Explants were precultured in the dark at 23 °C, in liquid MS medium with a progressively increasing sucrose concentration (0.3 M for 15 h, then 0.7 M for 5 h). Loading involved a 30 min incubation of explants in a solution comprising 1.9 M glycerol and 0.5 M sucrose. Explants were dehydrated at room temperature using a solution PVS A3 [Murashige and Skoog (MS) liquid medium, 22.5% (w/v) sucrose, 37.5% (w/v) glycerol, 15% (w/v) ethylene glycol and 15% (w/v) dimethylsulfoxide] for 30, 40 and 50 min and the PVS3 solution [MS liquid medium, 50% (w/v) sucrose, 50% (w/v) glycerol] for 60, 90 and 120 min. Explants were cooled by direct immersion in liquid nitrogen (LN) in 10 μl droplets of vitrification solution placed on aluminum foil strips. The foil strips were retrieved from LN and immersed in preheated (37 °C) unloading solution (0.8 M sucrose) for 30 s, and an equal volume of unloading solution at room temperature was added for further incubation for 30 min. Shoot tips were transferred onto the regrowth medium, cultivated in the dark for 7 days before being incubated under standard conditions.